Assessing the Economic Value of Vegetation in Northern Ghana's White Volta Basin: A Community Perspective - Bizoola, Gandaa Z. (Research Advances in Environment, Geography and Earth Science Vol. 10, 2024)
Potential income sources for rural communities can be identified by identifying market opportunities for selling vegetation to improve the livelihoods and financial stability of households, which determines the viability and demand for vegetation products in local markets. Concepts of ecosystem services have been developed to make explicit connections between human welfare and ecological sustainability for policy, development, and conservation initiatives. Economic concepts such as the distinction between prices and values, and the acknowledgment of their values are context-specific which may change across space and time. Concepts of ecosystem services have been developed to make explicit connections between human welfare and ecological sustainability for policy, development, and conservation initiatives. Economic concepts such as the distinction between prices and values, and the acknowledgment of their values are context-specific which may change across space and time. Contingent valuation is a survey-based economic technique for valuing non-market resources, such as vegetation. This method is often used to establish the amount people are willing to be compensated for maintaining the existence of an environmental feature such as a tree, shrub, or grass. The level of importance attached to provisioning services as well as cultural services and cultural heritage differ in the rural communities hence different cash values attached. It is often perceived that rural community members do not put a monetary value on vegetation, the study is therefore aimed at establishing the monetary value rural communities have for vegetation. The study was conducted in two irrigated and two unirrigated landscapes consisting of about 54 communities and comprising 240 respondents. Participatory Rural Appraisal tools were used. Random Utility Theory was applied and used for the analysis. The concerning native, sex, age, education, and household head. Marital status was, however, not significant in all the landscapes. Respondents’ willingness to accept a sell price of the various vegetation reached acceptable prices that gave average prices. The price trend is observed to be across a landscape, from the catchment to the downstream ecosystem. The study’s conclusion asserts that rural farmers in the targeted area have very good knowledge of the usefulness of vegetation to ecosystem services in their environment. However, it was observed that community members do not have much knowledge on the monetary value of vegetation and hence, it is important for awareness creation and up-date on the monetary value of ecosystem services.